COMPARATIVE STUDY ON URBAN TRANSPORT AND THE ENVIRONMENT (CUTE) FRAMEWORK AS STRATEGY FOR THE REDUCTION OF CARBON DIOXIDE EMISSIONS OF ROAD VEHICLES AT ZAPOTE STREET - L. Acierto, Joanna Marie; H. Quilla, Susane Marie; N. Valencia, Bobby Joel; L. Cueto, Geoffrey; F. Monjardin, Cris Edward; Wan Mohamed, Wan Mazlina (PLANNING MALAYSIA, 2023)
Carbon emissions from vehicles contribute significantly to carbon footprint production, which is one of the primary causes of climate change. In Caloocan City, increasing air pollution is observed despite the drastic decrease in air pollutants in major Metro Manila cities. This study primarily aims to provide strategies to reduce carbon dioxide emissions in Zapote St., Caloocan City, through a Comparative study on Urban Transport and the Environment (CUTE) Framework. The study identified that the hourly average carbon footprint contributed by private and public vehicles along Zapote Street is 686.27 and 243.71 kg CO2e on weekdays and 634.65 and 212.97 kg CO2e on weekends. The exploratory data analysis via Python shows that only the vehicle and fuel types affect the emissions volume. Accordingly, the Unified Vehicular Volume Reduction Program (UVVRP) was ineffective. It only resulted in additional private vehicles and increased congestion, indicating the need for an improved public transport system to encourage Filipinos to shift to public transport. Furthermore, the Traffic Volume Emission Projection (TVEP) model projects a decrease of 87.19 kg CO2e per hour in 2023 and 164.72 kg CO2e per hour by 2052, resulting from the 20% reduction in volume upon the implementation of the "no exemption of motorcycles" in the number coding scheme of Caloocan city.